Analyses of asthma severity phenotypes and inflammatory proteins in subjects stratified by sputum granulocytes - Hastie, Annette T.; Moore, Wendy C.; Meyers, Deborah A.; Vestal, Penny L.; Li, Huashi; Peters, Stephen P.; Bleecker, Eugene R. (Journal of allergy and clinical immunology, 2010)
Patients with severe asthma have increased granulocytes in their sputum compared with patients with mild to moderate asthma. We hypothesized that inflammatory granulocytes in sputum may identify specific asthma severity phenotypes and are associated with different patterns of inflammatory proteins in sputum supernatants. This hypothesis was tested in 242 patients with asthma enrolled in the Severe Asthma Research Program who provided sputum samples for cell count, differential cell determinations, cell lysates for Western blot, and supernatant analyses by inflammatory protein microarrays and ELISAs. ANOVA and multiple linear regression models tested mediator associations. Stratified by sputum granulocytes, <2% or ≥2% eosinophils and <40% or ≥40% neutrophils, subjects with both increased eosinophils and neutrophils had the lowest lung function and increased symptoms and health care use. Subjects with elevated eosinophils with or without increased neutrophils had significantly increased fraction exhaled nitric oxide (FeNO) and serum eosinophils and greater frequency of daily β-agonist use. Microarray data stratified by granulocytes revealed 25 to 28 inflammatory proteins increased >2-fold in sputa with ≥40% neutrophils. Microarray analyses stratified by severity of asthma identified 6 to 9 proteins increased >2-fold in sputa in subjects with severe asthma compared with nonsevere asthma. ELISA data stratified by sputum granulocytes showed significant increases in brain-derived neurotrophic factor, IL-1β, and macrophage inflammatory protein 3α/CCL20 for those with ≥40% neutrophils; these mediators demonstrated positive associations with neutrophil counts. Combined increased sputum eosinophils and neutrophils identified patients with asthma with the lowest lung function, worse asthma control, and increased symptoms and health care requirements. Inflammatory protein analyses of sputum supernatants found novel mediators increased in patients with asthma, predominantly associated with increased sputum neutrophils.